Docosahexaenoic Acid Improves the Nitroso-Redox Balance and Reduces VEGF-Mediated Angiogenic Signaling in Microvascular Endothelial Cells - Matesanz, Nuria (Association for Research in Vision and Ophthalmology, Inc., 2010)
PURPOSE. Disturbances to the cellular production of nitric oxide (NO) and superoxide (O(2)(−)) can have deleterious effects on retinal vascular integrity and angiogenic signaling. Dietary agents that could modulate the production of these signaling molecules from their likely enzymatic sources, endothelial nitric oxide synthase (eNOS) and NADPH oxidase, would therefore have a major beneficial effect on retinal vascular disease. The effect of ω-3 polyunsaturated fatty acids (PUFAs) on angiogenic signaling and NO/superoxide production in retinal microvascular endothelial cells (RMECs) was investigated. METHODS. Primary RMECs were treated with docosahexaenoic acid (DHA) or eicosapentaenoic acid (EPA) for 48 hours. RMEC migration was determined by scratch-wound assay, proliferation by the incorporation of BrdU, and angiogenic sprouting using a three-dimensional model of in vitro angiogenesis. NO production was quantified by Griess assay, and phospho-eNOS accumulation and superoxide were measured using the fluorescent probe dihydroethidine. eNOS localization to caveolin-rich microdomains was determined by Western blot analysis after subfractionation on a linear sucrose gradient. RESULTS. DHA treatment increased nitrite and decreased superoxide production, which correlated with the displacement of eNOS from caveolar subdomains and colocalization with the negative regulator caveolin-1. In addition, both ω-3 PUFAs demonstrated reduced responsiveness to VEGF-stimulated superoxide and nitrite release and significantly impaired endothelial wound healing, proliferation, and angiogenic sprout formation. CONCLUSIONS. DHA improves NO bioavailability, decreases O(2)(−) production, and blunts VEGF-mediated angiogenic signaling. These findings suggest a role for ω-3 PUFAs, particularly DHA, in maintaining vascular integrity while reducing pathologic retinal neovascularization.